CP and Bell's inequality violation in the neutrino-antineutrino oscillations - S M Saberi Fathi; N Imani (Iranian Journal of Physics Research, 2021)
Bell's inequality has made the ability to find nonlocality in what happened by a numerical indicator. CP violation is one of the most important phenomena that occur in nature. It represents asymmetry in the matter and anti-matter in the universe. In this paper, we use a thought experiment to obtain a formalism of Bell's inequality of type CHSH for Majorana neutrino. This inequality is sensible to CP violation.